Kurdayetî and Kurdish Nationalism: The Need for Distinction. (1st July 2018) - Tunc, Huseyin
Abstract : This article seeks to contextualize Kurdayetî (Kurdishness) in the broader debate on Kurdish nationalism. Existing accounts lack a clear definition of Kurdayetî and seldom contextualize it; yet treat Kurdayetî as a full-fledged Kurdish nationalism. As a result, the existing scholarship erroneously uses Kurdayetî and Kurdish nationalism interchangeably. In this article, I address this gap. I place Kurdayetî into the broader theoretical debate on the Kurdish nation, national identity, and nationalism. I argue that Kurdayetî signifies what Hobsbawm calls "proto-national bonds" or is equivalent to Smith's notion of "ethnie." Therefore, Kurdayetî is not equivalent to or synonymous with Kurdish nationalism, and thus it should not be used interchangeably.